2002
DOI: 10.1051/rnd:2002033
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of cortisol and oxytocin, and uterine activity after cervical artificial insemination in the ewe

Abstract: -The objective was to compare in the ewe the effects of easy and difficult procedures for artificial insemination (AI) (as related to rapid or poor accessibility of the cervix, respectively) on plasma cortisol (CORT) and oxytocin (OT), and uterine motility. All AI were simulated using a catheter empty of semen to study genital and environmental stimuli only. In experiment 1, 40 ewes were sampled after AI, and whether it was an easy or difficult procedure was reported for each animal. While CORT concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Although uterine activity was not recorded in the present study, it is probable that uterine activity increased during insemination, as reported in ewes (Lehrer et al, 1979;Houdeau et al, 2002), mares (Troedsson et al, 1998) and women (Sahmay et al, 1990). In the ewe, by analysing the AI operation gesture step-by-step, it appeared that both introduction and opening of the speculum in the vagina, then searching of the cervical canal for the correct site of semen deposition evoked autonomic nerve-mediated uterine contractions that considerably differed from the normal motor pattern observed during natural mating (Raynal and Houdeau, 2004).…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Although uterine activity was not recorded in the present study, it is probable that uterine activity increased during insemination, as reported in ewes (Lehrer et al, 1979;Houdeau et al, 2002), mares (Troedsson et al, 1998) and women (Sahmay et al, 1990). In the ewe, by analysing the AI operation gesture step-by-step, it appeared that both introduction and opening of the speculum in the vagina, then searching of the cervical canal for the correct site of semen deposition evoked autonomic nerve-mediated uterine contractions that considerably differed from the normal motor pattern observed during natural mating (Raynal and Houdeau, 2004).…”
Section: Discussionmentioning
confidence: 39%
“…It may be that these females were inseminated too early in relation to the ovulation time, which is known to decrease fertilily in goats (Maurel et al, 1992). On the other hand, we have previously shown in the ewe that genital stimulation during AI enhanced uterine motility (Houdeau et al, 2002;Raynal and Houdeau, 2004), and previous studies highlighted a negative correlation between increased uterine motility at the time of AI and fertility rates in small ruminants (Lightfoot and Restall, 1971;Toutain et al, 1985), and also in women Leyendecker et al, 1996). From the perspectives of the AI technique, the longer the duration of insemination, the more mechanical stimulation is experienced by the vagina and cervix by the AI apparatus, often due to the difficulty of reaching the cervical canal with the insemination gun.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In all cases, there is considerable between-ewe variation in the occurrence and strength of the cervical response, which perhaps may be a clue to why conception, following cervical deposition of frozen-thawed semen, seems to occur with apparent ease in some ewes but not others. The stimulatory effect of oxytocin is particularly interesting in that Houdeau et al (2002) found that a significant increase in oxytocin release only occurred following poor, as opposed to rapid, access to the cervix at insemination with the effect on uterine activity lasting for a mean 6 s.e.m., of 15 6 4 min following a difficult insemination compared with 2 6 1 for an easy one. Although the stress response, as measured by the elevation in plasma cortisol was similar for both categories, it may be that the oxytocin-induced extension of uterine activity had an adverse effect on cervical sperm transport.…”
Section: Cervical Activitymentioning
confidence: 99%
“…Some authors have questioned the fact that the cervical AI technique causes stress in animals compared to the laparoscopic technique, leading to increased levels of cortisol and consequently interference with the ovulation rates, causing low fertility in induction protocols and in synchronizing estrus and ovulation (HOUDEAU et al, 2002;BREEN et al, 2005).…”
Section: Introductionmentioning
confidence: 99%